STUDI ETNOGRAFI TENTANG STRATEGI SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Khumaeroh, Dewi; Charenta, Anggun Hana; Fadlullah, Ridwan; Ermawati, Diana (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to explore the strategies of fourth grade elementary school students in solving math story problems and their inhibiting factors. The approach used was qualitative with ethnographic methods, conducted at SD 3 Wergu Wetan, Kudus. Participants consisted of fourth grade teachers and 10 students who were selected purposively. Data were collected through in-depth interviews, participant observation in the classroom, and document analysis in the form of student work. Data analysis used the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of interviews, observations, and documentation. The results showed that students used strategies such as repeated reading, identifying information, drawing, and working with friends. Barriers found included low reading ability, lack of understanding of basic mathematical concepts, as well as the post-pandemic impact on learning behavior. Teachers observed students' difficulties in understanding the problems and realized the importance of improving reading skills and math concepts. Teachers' efforts include reinforcement of basic math, repetition of material, interesting approaches, and peer tutors. This study emphasizes the importance of reading skills, mastery of basic mathematics concepts, and adaptive learning strategies to improve students' ability in mathematics story problems.